Tekanan Fiskal dan Fragmentasi Anggaran Ketahanan Pangan Kabupaten Mamuju Tengah 2023–2025 - Andi Faisal; Adriansyah Adriansyah; Nurlina Nurlina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study examines the budgetary dynamics of the Regional Budget (APBD) of Central Mamuju Regency for the period 2023–2025 within the context of fiscal constraints and food security policy adaptation. Employing document analysis and secondary data methods, the study identifies three main patterns: (1) structural fiscal pressure marked by the dominance of personnel expenditure reaching 46.07% of total expenditure in 2025; (2) fragmentation of food security budgets, evidenced by a decline in food sector allocations from IDR 18.27 billion (2023) to IDR 4.14 billion (2025); and (3) budget revision as a strategic adaptation mechanism, particularly in 2025 where food sector budget increased by 284% from the initial budget. Findings indicate that local governments tend to use budget revision mechanisms as responsive instruments, yet this approach remains reactive and does not reflect a planned catalytic governance role. The study's implications point to the importance of reconstructing catalytic-based budgeting strategies under conditions of fiscal constraint.